'Happy amicable co-operation': mutual aid, anarchism and the image of the bee in the work of Louisa Sarah Bevington. (2nd January 2017) - Funk, Wolfgang
Abstract: The poet and political activist Louisa Sarah Bevington has been largely ignored in accounts of late Victorian literary and cultural history, even though her work presents a singular nexus of scientific, socio-cultural and poetical perspectives. This essay will show how Bevington juxtaposes Social Darwinist interpretations of the theory of evolution, which foreground the idea of human life as a struggle for existence, with the anarcho-communist view proposed by Peter Kropotkin, which foregrounds the human capacity for sympathy and mutual aid as the driving forces in social development. After situating Kropotkin's ideas within the larger context of anarchist and evolutionist thinking, the article illustrates central aspects of his scientific and political agenda in Bevington's essays, pamphlets and poems. The essay pays particular attention to the images of the bee and beehive, which function as symbols for an idealised version of anarchist society.